Akibat Hukum Perjanjian Pinjam Nama Atas Kepemilikan Tanah WNA dalam Perspektif Hukum Perdata Internasional - Clara, Anggi Dwita; Novia, Elsa Ari; Astuti, Retno Dwi; Hotimah, Husnul; Buana, Vaddeli Bagas; Wijaya, Mustika Mega (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Based on article 21 of the Basic Agrarian Law which states that only Indonesian citizens can be given permission to own land in Indonesian territory. This normative analytical descriptive juridical research describes an examination of the legal certainty of the Nominee Agreement regarding the legitimacy of the transfer of property rights in accordance with national laws and regulations. The large number of mobilization activities of foreigners in Indonesia, especially in tourist areas, has made many foreigners decide to settle in Indonesia. Due to the large number of foreigners living in Indonesia, legal violations occur. One of them is legal smuggling of name loan agreements which are based on the theory of legal certainty, agreement theory and share ownership theory which are invalid and do not meet the objective requirements in BW. The juridical impact of this name-borrowing agreement is that it creates defects both legally and in terms of the legality of the agreement, thereby facilitating disagreements about who owns the land which will give rise to legal uncertainty and disputes in the future. If one of the parties defaults, there will be no legal consequences in the form of sanctions against the violator because the agreement that is the basis of the agreement violates statutory regulations and violates the law.